Study of a new glass matrix by thermoluminescent technique for high-dose dosimetry (Brazilian Journal of Radiation Sciences, 2017)
The thermoluminescence technique is widely used for both personal and high-dose dosimetry. In this work, the thermoluminescence technique was utilized to study a new glass matrix, with nominal composition of 20Li2CO3.10Al2O3.30BaO.40B2O3 (mol%), irradiated with different doses in a 60Co source. The glow curves and the dose-response curve were obtained for radiation doses of 10, 50, 100, 200 and 700 Gy. The results showed that this new glass matrix has potential use in high-dose dosimetry.